Managerial accounting - Braun, Karen Wilken
Authors Wendy Tietz, Karen Braun, and Walter Harrison show the connection between accounting concepts and the businesses students interact with in their new text, Managerial Accounting. By presenting the accounting decisions made in companies like Target and J. Crew, this text's precise coverage of the core concepts--combined with the unlimited practice in MyAccountingLab, the text's market-leading online homework and tutorial program--gets students engaged in the learning process. With Managerial Accounting and MyAccountingLab, students will have more "I Get It!" moments and leave the course with a rock-solid understanding of managerial accounting. For this edition, Wendy Tietz, of Kent State University, contributed as coauthor. Dr. Tietz is an award-winning and experienced accounting and technology educator. Together, the authors refined their philosophy for the end-of-chapter and supplementary material for the second edition